2017
DOI: 10.1097/md.0000000000006225
|View full text |Cite
|
Sign up to set email alerts
|

A case of mixed adenoneuroendocrine carcinoma of the pancreas

Abstract: Rationale:Tumors with multiple histological features, such as adenocarcinomas and neuroendocrine carcinomas, were included as a new category of neuroendocrine carcinomas in the 2010 World Health Organization classification. We recently experienced a rare case of a pancreatic carcinoma with both adenocarcinoma and neuroendocrine carcinoma components, a so-called mixed adenoneuroendocrine carcinoma.Patient concerns and diagnosis:A 66-year-old man was referred to our hospital with obstructive jaundice. Contrast-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…For example, one study that reported a case of mixed adenoneuroendocrine carcinoma of the pancreas, examined the two different components by immunostaining and found that the tumour protein p53 was positive in both tumour components. 15 This finding supports the hypothesis that they were derived from a single cancer stem cell. In the second hypothesis, the lesions are thought to develop as two distinct tumours derived from two different precursors.…”
Section: Discussionsupporting
confidence: 81%
“…For example, one study that reported a case of mixed adenoneuroendocrine carcinoma of the pancreas, examined the two different components by immunostaining and found that the tumour protein p53 was positive in both tumour components. 15 This finding supports the hypothesis that they were derived from a single cancer stem cell. In the second hypothesis, the lesions are thought to develop as two distinct tumours derived from two different precursors.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, in a case report of a collision tumor of poorly differentiated cecal adenocarcinoma with signet ring cell and mucinous features admixed with a well differentiated neuroendocrine tumor, next generation sequencing showed BRCA2 mutation in both the adenocarcinoma and NET components, while a TP53 mutation was only found in the adenocarcinoma component, with no mutations of KRAS , NRAS or BRAF in either component[ 47 ]. Immunohistochemical studies in a case a mixed adenoneuroendocrine carcinoma of the pancreas suggests NEC as the precursor giving rise to the adenocarcinoma component, with both of them diverging from a single cancer stem cell[ 62 , 63 ]. Immunohistochemistry study of seven colorectal MANEC as part of a study of gastrointestinal MANECs by Gurzu et al [ 64 ] in 2019 reports that gastrointestinal MANEC is a microsatellite stable tumor with strong positivity to CD44 and no expression of maspin suggesting an origin from a CD44-positive stem like precursor cell.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of any specific radiologic or symptomatic predictors of the tumor, the diagnosis is made based on the histopathological findings. Although the etiopathogenesis of the tumor is completely unclear, immunohistochemical studies have confirmed that the NEC component may give rise to the adenocarcinoma component, with both of them deriving from a single stem cell ( 16 ). Till date, in the published literature, MANECs have been identified in various localizations, with the colon ( 7 ) and the stomach ( 6 ) being the most common.…”
Section: Discussionmentioning
confidence: 99%